Classification of Women in The Class Concept of Dowry: A Study of Berger and Luckmann's Social Construction - Ahmad Arif Masdar Hilmy; Ria Cahyaning Utami (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
The determination of the dowry in the marriage of the people of Karangsono Village was originally based on the rules of Islamic law, namely by using the principles of convenience, lightness, and simplicity. However, people's lives that are never stagnant make them always interact with each other, thus forming a new concept of dowry determination in the community. The purpose of this article is to determine the description and implementation of the concept of the dowry class in the community marriage of Karangsono Village and to review it using the perspective of the social construction theory. This field research used a qualitative descriptive method and data analysis used Berger and Luckmann's social construction theory. Data were collected through document study, interviews, and observations. This research resulted in conclusions: (1) The concept of the dowry class in the community marriage of Karangsono Village is based on the classification of the prospective bride, which is seen from the status of a virgin or widow, her beauty, and age. The higher the quality of the woman, the higher the dowry she can get, (2) The determination of the dowry in Karangsono Village has undergone a social construction based on three simultaneous processes. The externalization process is illustrated through adaptation to religious texts and life being experienced. The process of objectivation here gives birth to new meanings, which are manifested in the actions of the wider community so that they become objective facts. The process of internalization is illustrated by the affirmation in the consciousness experienced subjectively.(Penentuan mahar dalam perkawinan masyarakat Desa Karangsono mulanya didasarkan pada aturan hukum Islam, yakni dengan menggunakan asas kemudahan, keringanan dan kesederhanaan. Namun kehidupan masyarakat yang tidak pernah stagnan, membuat mereka selalu berinteraksi satu sama lain, Tujuan artikel ini ialah untuk mengetahui deskripsi dan implementasi konsep kelas mahar dalam perkawinan masyarakat Desa Karangsono, serta ditinjau menggunakan perspektif teori konstruksi sosial. Penelitian lapangan ini menggunakan metode deskriptif kualitatif dan analisis datanya menggunakan teori konstruksi sosial Berger dan Luckmann. Pengambilan data dilakukan melalui studi dokumen, wawancara dan observasi. Penelitian ini menghasilkan beberapa kesimpulan: (1) Konsep kelas mahar dalam perkawinan masyarakat Desa Karangsono ialah berdasarkan klasifikasi yang dimiliki calon pengantin perempuan, yakni dilihat dari status perawan atau janda, paras kecantikan dan usianya. Semakin tinggi kualitas yang dimiliki perempuan, maka semakin tinggi pula mahar yang bisa didapatkannya, (2) Penentuan mahar di Desa Karangsono telah mengalami konstruksi sosial berdasarkan tiga proses simultan. Proses eksternalisasi tergambar melalui adaptasi dengan teks-teks keagamaan dan kehidupan yang sedang dialami. Proses objektivasi disini melahirkan pemaknaan baru, yang termanifestasikan ke dalam tindakan-tindakan masyarakat luas sehingga menjadi kenyataan objektif dan biasa dilakukan dalam kehidupan sehari-hari. Proses internalisasi tergambar oleh penegasan dalam kesadaran yang dialami secara subjektif dan pentransferan akan pengetahuan tentang makna-makna objektif)